TELAAH KRITIS TERHADAP TAFSIR FEMINIS ATAS KISAH RATU BALQIS SEBAGAI LEGITIMASI KEPEMIMPINAN PEREMPUAN - Nabila Zhafira Liana; Syafii Syafii; Mochammad Novendri Saputra (STAI Asy-Syukriyyah, 2026)
This study examines feminist interpretations of the story of Queen Balqis in Surah An-Naml verses 22–44 and its relevance to the legitimacy of women’s leadership in Islam. This research employs a qualitative approach through library research by analyzing classical and feminist tafsir. The findings show that classical exegetes such as Al-Tabari, Al-Qurtubi, and Ibn Kathir understood the story of Queen Balqis as a theological narrative emphasizing monotheism and the acceptance of divine guidance, rather than as a normative legitimization of women’s leadership. Meanwhile, feminist exegetes such as Amina Wadud and Abla Hasan interpret the story as a representation of rational and dialogical female leadership. However, feminist tafsir is considered to have methodological limitations due to its reliance on hermeneutical approaches, selective use of scriptural evidence, and tendency to overlook hadith and the understanding of the majority of early Muslim scholars (salaf). This study concludes that the story of Queen Balqis is more appropriately understood as a moral and theological lesson rather than a normative legitimization of women’s leadership in Islam. Keywords: Feminist exegesis, Queen of Sheba, women’s leadership, Surah An-Naml, classical exegesis